Epidural anesthesia masking pain from spinal epidural hematoma - Kokubo, Rinko; Kim, Kyongsong; Kim, Chol; Matsuda, Akihisa; Morita, Akio (Nepal Journal of Neuroscience, 2019)
Spinal epidural hematoma (SEDH) without pain due to epidural anesthesia is a rare but serious complication. We report the successful treatment of a patient with progressive paraparesis after the development of SEDH during the administration of epidural anesthesia. An 84-year-old woman underwent laparoscopy with epidural anesthesia. To prevent deep vein thrombosis, the delivery of low molecular weight heparin was started 16.5 hours after laparoscopy. On the 1st postoperative day she reported painless leg paralysis and on the 2nd day she manifested severe paraplegia and urinary retention. Magnetic resonance imaging revealed an SEDH compressing the spinal cord at the Th12 - L1 and we performed emergent laminectomy. After the laminectomy her symptoms disappeared completely. SEDH is a rare but serious complication related to epidural anesthesia. As its excessive analgesic effect may elicit motor weakness and mask pain, SEDH must be ruled out in patients with paraparesis with continuous epidural anesthesia.